Generation of fleshings at beamhouse in tannery and its environmental impact assessment: Bangladesh perspective (Bangladesh Journal of Scientific and Industrial Research, 2015)
Leather processing involves the conversion of putrescible hide/skin into imputrescible leather and consequently huge amount of solid waste generated in tanning process. In tannery at beamhouse, fleshing is one of the most indispensable mechanical operations in leather processing where significant amount of solid waste (termed as fleshings) is produced. A work was carried out to estimate the generated fleshing and to assess its environmental impact. In Bangladesh yearly 20.1×103 MT fleshings was generated only from cow hide and goat skin where 10.3×103 MT for cow hide and 9.8×103 MT for goat skin. The generated fleshings are usually kept indiscriminately inside or outside the industrial area as green. In rainy season, all fleshings including other solid wastes are washed away and finally fall in to the river, Buriganga. Fleshings contained alkaline pH (12.3±0.2), fat, proteins, lime and sulphide. Improper management of fleshings has negative effect on human health, air, water, land and plant.Bangladesh J. Sci. Ind. Res. 50(3), 227-232, 2015